Microservices in Scala - Lelek, Tomasz; Safari eBooks ([Place of publication not identified] : Packt Publishing, 2017)
"Microservices is an architectural style and pattern that is becoming hugely popular and is adopted by many organizations because of the advantages that it offers. It is an approach to building asynchronous, non-blocking, and failure-resilient applications. This course focuses on building microservices in Scala. It addresses the best practices and common pitfalls in microservice architecture and useful implementation strategies in Scala. We start by shedding light on traditional monoliths, Service Oriented Architecture (SOA), and how microservices evolved from it. Next we move on to explain the Play framework and build a small but working application. You will understand the importance of writing code that is asynchronous and non-blocking and how Play helps us do this. Later, the video explains how to build Reactive microservices using Akka and Akka HTTP, which adhere to the principles underlying the Reactive Manifesto. Next, we explore building high-throughput and resilient applications in some detail. At the end of the video, we explore Lagom and how it incorporates best practices to avoid common pitfalls."--Resource description page.
Presenter, Tomasz Lelek.
Title from title screen (viewed June 29, 2017).
Date of publication from resource description page.
Keywords: Computer architecture; Computer software -- Development; Scala (Computer program language); Distributed operating systems (Computers); Electronic books